2005
DOI: 10.1063/1.2052027
|View full text |Cite
|
Sign up to set email alerts
|

Development of a virtual probe tip with an application to high aspect ratio microscale features

Abstract: Nondestructive measurement of microscale features remains a challenging metrology problem. For example, to assess a high aspect ratio small hole it is currently common to cut a cross section and measure the features of interest using an atomic force microscope, scanning probe microscope, or scanning electron microscope. Typically, these metrology tools may be suitable for surface finish measurement but often lack the capability for dimensional metrology. The aim of this article is to discuss the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
28
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…However, it is very difficult to precisely measure the shapes of micro-holes that have large length/diameter (L/D) ratios because of the difficulties encountered during probe fabrication and the complexities involved in employing a sensing method that uses a small measuring force. Many studies have been reported on micro-hole measurement techniques employing a variety of probes such as optical probes [1][2][3], vibroscanning probes [4,5], vibrating probes [6][7][8][9][10][11][12], tunneling effect probes [12,13], opto-tactile probes [14], fiber probes [15,16], optical trapping probes [17], and diaphragm or flexure based probes using an elastic mechanism [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is very difficult to precisely measure the shapes of micro-holes that have large length/diameter (L/D) ratios because of the difficulties encountered during probe fabrication and the complexities involved in employing a sensing method that uses a small measuring force. Many studies have been reported on micro-hole measurement techniques employing a variety of probes such as optical probes [1][2][3], vibroscanning probes [4,5], vibrating probes [6][7][8][9][10][11][12], tunneling effect probes [12,13], opto-tactile probes [14], fiber probes [15,16], optical trapping probes [17], and diaphragm or flexure based probes using an elastic mechanism [18][19][20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the contact mode microprobes usually apply styli with a limited aspect ratio to achieve a better measurement stability. To mitigate these problems, non-contact mode micro-CMM probes have been developed [21][22][23]. In the non-contact measurement mode, the probes are vibrated and the change of the vibration amplitude due to the probe sample's interaction is usually applied for measurements.…”
Section: Introductionmentioning
confidence: 99%
“…In the non-contact measurement mode, the probes are vibrated and the change of the vibration amplitude due to the probe sample's interaction is usually applied for measurements. For instance, Bauza et al [21] developed a high-aspect-ratio microprobe using a probe shank with a diameter of 7 µm having an aspect ratio of 700:1. During the measurements, its probe shank is oscillated in a standing wave.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been reported on micro hole measurement techniques that employ a variety of probes, such as optical probes, vibroscanning probes, vibrating probes, tunneling effect probes, opto-tactile probes, fiber deflection probes, optical trapping probes, diaphragm probes [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], among others. This paper presents a system of micro hole measurement using an optical fiber probe that is available as a low-force displacement probe and has a wide measuring range [16].…”
Section: Introductionmentioning
confidence: 99%